Adverse childhood experiences and early adolescent cyberbullying in the United States. Issue 3 (28th November 2022) - Nagata, Jason M.; Trompeter, Nora; Singh, Gurbinder; Raney, Julia; Ganson, Kyle T.; Testa, Alexander; Jackson, Dylan B.; Murray, Stuart B.; Baker, Fiona C.
Abstract: Introduction: With the increasing use of social media and online platforms among adolescents, the relationship between traumatic life events and cyberbullying remains unclear. This study aimed to determine the associations between adverse childhood experiences (ACEs) and cyberbullying victimization among a racially/ethnically and socioeconomically diverse sample of early adolescents. Methods: We analyzed longitudinal data from 10, 317 participants in the Adolescent Brain Cognitive Development (ABCD) study, baseline (2016–2018, ages 9–10 years) to Year 2. Logistic regression analyses were used to estimate associations between ACEs and cyberbullying victimization, adjusting for sex, race/ethnicity, country of birth, household income, parental education, and study site. Results: In the sample (48.7% female, 46.0% racial/ethnic minority), 81.3% of early adolescents reported at least one ACE, and 9.6% reported cyberbullying victimization. In general, there was a dose–response relationship between the number of ACEs and cyberbullying victimization, as two (adjusted odds ratio [AOR]: 1.45, 95% confidence interval [CI]: 1.13–1.85), three (AOR: 2.08, 95% CI: 1.57–2.74), and four or more (AOR: 2.37, 95% CI: 1.61–3.49) ACEs were associated with cyberbullying victimization in adjusted models. In models examining the specific type of ACE, sexual abuse (AOR: 2.27, 95% CI: 1.26–4.11), physical neglect (AOR: 1.61, 95% CI: 1.24–2.09), and household mental health problems (AOR: 1.39, 95% CI: 1.18–1.65) had the strongest associations with cyberbullying victimization. Conclusion: Adolescents who have experienced ACEs are at greater risk for experiencing cyberbullying. Interventions to prevent cyberbullying could use a trauma‐informed framework, including inter‐peer interventions to break this cycle of trauma.